2010
DOI: 10.1038/nrd3148
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide

Abstract: In January 2010, liraglutide (Victoza; Novo Nordisk)--an injectable glucagon-like peptide 1 receptor agonist--was approved by the US FDA to improve glycaemic control in adults with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
119
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 13 publications
1
119
0
1
Order By: Relevance
“…Clinical studies revealed that replacement therapies with metabolically stable GLP-1 mimetics, or treatment with dipeptidyl peptidase-IV inhibitors, can improve the management of hyperglycemia for some patients. Both exenatide (Byetta; Amylin Pharmaceuticals, Inc., San Diego, CA) and liraglutide (Victoza; Novo Nordisk A/S, Bagsvaerd, Denmark) have been approved by the U.S. Food and Drug Administration for the treatment of type II diabetes (Kolterman et al, 2003;Drucker et al, 2010). However, as peptide analogs of GLP-1, these require administration by intravenous or subcutaneous injection and have been associated with significant adverse side effects, including pan-creatitis (Olansky, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies revealed that replacement therapies with metabolically stable GLP-1 mimetics, or treatment with dipeptidyl peptidase-IV inhibitors, can improve the management of hyperglycemia for some patients. Both exenatide (Byetta; Amylin Pharmaceuticals, Inc., San Diego, CA) and liraglutide (Victoza; Novo Nordisk A/S, Bagsvaerd, Denmark) have been approved by the U.S. Food and Drug Administration for the treatment of type II diabetes (Kolterman et al, 2003;Drucker et al, 2010). However, as peptide analogs of GLP-1, these require administration by intravenous or subcutaneous injection and have been associated with significant adverse side effects, including pan-creatitis (Olansky, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to EX-4 (Bachem, Torrance, CA), another GLP-1 analog has been approved for the treatment of type 2 diabetes, i.e., liraglutide (Victoza; Novo Nordisk, Princeton, NJ). Liralgutide possesses an extended plasma half-life, similarly to EX-4, via a fatty acid acylation mechanism (Chapter et al, 2010;Drucker et al, 2010). Another mechanism of GLP-1 modification that has demonstrated therapeutic potential is fusion of the GLP-1 dimer with recombinant human albumin, producing albiglutide (Baggio et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One of the FDA-approved GLP-1R agonists is liraglutide which is used to treat type 2 diabetes (23). Liraglutide has a 97% homology with human GLP-1 including a lysine to arginine mutation at position 34 and a palmitoyl side-chain at lysine 26 (24).…”
mentioning
confidence: 99%